Custo Total de Propriedade Aplicado à Migração de Sistemas Legados para Ambiente de Computação em Nuvem - MAIA, Anilton Bezerra (2023)
With the widespread adoption of cloud adoption, one of the main challenges is the lack of a comprehensive strategy and deep understanding of the characteristics involved in migrating from legacy systems to the cloud computing environment, making adoption planning more intended. Migrating legacy systems to cloud platforms is costly, as well as requiring a rigid process that can validate operational costs, investments, technical and non-technical challenges. In this work, we present an approach based on total cost of ownership - TCO for decision-making on the migration of legacy systems to a cloud computing environment. In the experiments carried out, an 89% financial advantage was achieved in relation to the traditional model (on-premise), as well as other additional advantages such as security, availability and scalability. This demonstrates that the TCO-based approach is an effective solution for those looking to migrate their legacy systems to the cloud computing environment.